Information technologies in management of professional safety - Berezutskyi, Viacheslav; Luftman, Jerry (Національний технічний університет "Харківський політехнічний інститут", 2019)
The issues considered are the integration of IT technologies in the management of professional safety of employees and employees. An insufficient level of application of software at Ukraine in IT technologies is pervasive, which hinders the development of management in security matters. The possibilities of GIIM (USA) in providing education/training and certification in the field of managing IT technologies are shown.

Розглядаються питання інтеграції ІТ-технологій в управління професійною безпекою службовців. Недостатній рівень застосування програмного забезпечення в Україні в ІТ-технологіях широко поширений, що перешкоджає розвитку управління в питаннях безпеки. Показано можливості GIIM (США) щодо надання освіти / навчання та сертифікації у галузі управління ІТ-технологіями.
Інфрмаційні технології у вирішені питань менеджменту з професійної безпеки
Keywords: occupational safety; health; GIIM; ІТ; управління; охорона праці; здоров'я